Desenvolvimento e teor de alcalóides em plantas de ipeca (Cephaelis ipecacuanha, A. Richard) obtidas in vitro submetidas às condições nutricionais em casa de vegetação - Costa, Marly Pedroso da (1995)
The plants Cephaelis ipecacuanha, A. Richard., is amedicinal plant which has in its roots the active principie emetine, which is effectivelly utilized in the combat of amebian desintery. The aim of this work was to investigate the development and growth of plantlets from tissue culture relative to different leveis of mineral nutrition and its correlation with the production of alkaloid in the root system The plantlets were multiplied from internodal segments on Murashige and Skoog médium with 6,66 µM of benzyladenine (BAP) and shoots obtained were induced to rooting on MS médium with the halfthe concentrations ofthe salts, supplemented with 4,92 µM of IBA. Rooted plantlets were transplanted to pots in agreenhouse and subjected to nutritional regimes weekly, utilizing as a nutritive solution, the formulation of macro and micronutrients ofthe MS médium in the following concentrations: 0, 25%; 50% and 100%. The plants were evaluated during six, nine and twelve months of cultivation. In the period of six months, the concentration of 25% was the one which yield best induction of biosinthesis of the alkaloid emetine, greatest yield per dry matter accumalated in the root biomass production in the root system For nine months, 50% ofthe solution ofMS salts showed the best results. However, at twelve months when the highest sysnthesis ofthe alkaloid, it was verified that 100% of the solution was the best in inducing emetine. Meanwhile, the plants irrigated with the nutritive solution of 50%, reached highest yield of emetine in relation to the root system biomassa (110,37 mg).